Closeness or Distance? An Investigation of Employee–Organization Relationships: From a Psychological Distance Perspective - Li, Shanshan; Chen, Hong (Frontiers in Psychology, 2019)
It is of great significance to grasp and control the relationship between organizations and employees for the healthy development of an organization. This paper measured the closeness and distance of the employee–organization relationship. The results were based on an investigation of 554 employees. (1) The mean value of the employee–organization psychological distance (EOPD) was 3.51, indicating that the relationship between the employee and organization was not optimistic. (2) 48.79% of the 554 interviewees maintained “existence” relationships with their organizations, 28.13% of people maintained “exclude” relationships with their organizations, 20.44% had a “loyalty” relationship, while only 2.64% had an “integrated” relationship with their organization. (3) EOPD showed significant differences in terms of age, marital status, education, career, position and residence area. (4) Detailed analysis was undertaken to explore the distribution characteristics of four relationships, and specific rules were found. Our research provided a new perspective and related references for the further study of organizational management.